2009
DOI: 10.1186/1471-2458-9-215
|View full text |Cite
|
Sign up to set email alerts
|

Association of socioeconomic status with overall overweight and central obesity in men and women: the French Nutrition and Health Survey 2006

Abstract: Background: Identification of subpopulations at high risk of overweight and obesity is crucial for prevention and management of obesity in different socioeconomic status (SES) categories. The objective of the study was to describe disparities in the prevalence of overweight and obesity across socioeconomic status (SES) groups in 18-74 year-old French adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
67
5
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 38 publications
11
67
5
4
Order By: Relevance
“…Thus children of higher socioeconomic standing are nutritionally better, contribute more towards societal development and spend better quality life. The results have been validated by earlier findings 53,54 which showed that higher education and income were associated with a greater consumption of good quality foods, decreased consumption of energy dense foods and reduced risk of overweight and obesity. Gaps found in the educational and professional levels of the parents of adolescents attending public and private schools need to be plugged in through socio-economic development programs by investing more in social sectors i.e., education, nutrition, health, safe and clean drinking water, hygiene and sanitation and safety nets to combat food insecurity and poverty.…”
Section: Discussionsupporting
confidence: 72%
“…Thus children of higher socioeconomic standing are nutritionally better, contribute more towards societal development and spend better quality life. The results have been validated by earlier findings 53,54 which showed that higher education and income were associated with a greater consumption of good quality foods, decreased consumption of energy dense foods and reduced risk of overweight and obesity. Gaps found in the educational and professional levels of the parents of adolescents attending public and private schools need to be plugged in through socio-economic development programs by investing more in social sectors i.e., education, nutrition, health, safe and clean drinking water, hygiene and sanitation and safety nets to combat food insecurity and poverty.…”
Section: Discussionsupporting
confidence: 72%
“…Unlikely the mentioned studies and confirming the data found in the RFB 2008-2009 (16) and in the present study, other researchers have found higher prevalence of excess weight in males (19)(20)(21) . Regarding the prevalence of central obesity found, 84.0%, it was superior to those of other national surveys (19)(20) and international (20,21) . In these, as well as in the present study, women showed a higher prevalence of central obesity compared to men and a significant linear tendency as their age increase.…”
Section: Discussioncontrasting
confidence: 57%
“…Regarding the confounding variable occupational status, men with high intakes of fresh cheese and non-workers (currently in school, unemployed, disabled or retired or who did not work) seemed to be protected against overweight compared with those in work. Other authors, however, have found negative associations between occupational status and Ov/Ob in men (Vernay et al, 2009). Along similar lines, women with high intakes of processed cheese and unemployed, disabled, retired or not working are more likely to be Ob compared with those in work, in the present study.…”
Section: Discussionsupporting
confidence: 35%